Validitas Media Pembelajaran Powerpoint Interaktif Berbasis Canva Untuk Kemampuan Literasi Membaca Anak di TK B Yaspa - Khusnul Khotimah; Windi Dwi Andika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to address the lack of engaging and interactive digital learning media used in early reading activities at TK B Yaspa by developing an interactive PowerPoint media based on Canva. The research employed the first three stages of the 4D development model—define, design, and develop—ending at the validation phase. During the define stage, observations and teacher interviews revealed that children showed limited interest and required more visually appealing media to support early literacy. In the design stage, a flowchart and storyboard were created to guide the structure, content arrangement, and interactive features of the media. The develop stage involved producing the learning media by integrating child-friendly visuals, simple text, audio elements, and interactive navigation. The resulting product was then validated by material and media experts. The validation results showed that the media achieved 92.86% from the material expert and 92.5% from the media expert, both categorized as “Highly Valid.” These results indicate that the media is feasible and appropriate to support early reading literacy.